Developing Ethical Awareness Towards a Sustainable Ecosystem Through Character Education in Higher Education - Balontia, Meitty (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study explores the impact of character education in developing ethical awareness for ecosystem sustainability, focusing on BINUS University students through a project-based learning approach. The character education in question is education that is based on the principles of Pancasila, which emphasizes the development of ethical behavior, social responsibility, and collective action to maintain a sustainable ecosystem. This study explores the relationship between ethical awareness and ecosystems by analyzing the results of student projects and interviews. The results show that students recognize the importance of collaboration between individuals, governments, and other stakeholders in ensuring environmental sustainability. The main findings highlight three important aspects: collective ethical awareness, shared values, and sustainable benefits. Collective ethical awareness is a universal value where students understand that maintaining an ecosystem requires cooperation and moral responsibility. Shared values, especially those embedded in Pancasila, strengthen students' beliefs that justice for nature is a collective obligation between individuals and institutions. Sustainable benefits refer to the long-term benefits to the environment and society that arise from maintaining a sustainable ecosystem. This study concludes that character education is very important in shaping students' moral perspectives and actions towards environmental conservation. Through project-based learning, students develop a deeper understanding of the complex relationships between human activities and ecosystems, ultimately fostering resilient communities that can cope with rapid environmental change. This research underscores the importance of integrating ethics education into higher education for future environmentally conscious leaders.